Effect of storage time on moisture content of Reutealis trisperma seed and its effect on acid value of the isolated oil and produced biodiesel. (November 2019) - Abduh, Muhammad Yusuf; Syaripudin; Putri, Laksmitha Widyanie; Manurung, Robert
Abstract: Reutealis trisperma has been studied as an alternative source of producing biodiesel. Moisture content of Reutealis trisperma seed is very important to determine the quality of biodiesel produced from the oil isolated from Reutealis trisperma seed. This study investigated the time profile of moisture content for four different fractions of trisperma seed (PT-3, PT-7, PT-14, NPT-21) for four months. The moisture content of trisperma seeds was modelled using instationary diffusion equation. Total oil content in trisperma seed as well as acid value of the extracted oil from stored trisperma seed were periodically measured for four months. Acid value of trisperma oil obtained from the stored seed experienced an increase from 1.1 mg KOH/g to 2.8 mg KOH/g for PT-3, 1.9 mg KOH/g to 9.9 mg KOH/g for PT-7, 3.4 mg KOH/g to 11.6 mg KOH/g for PT-14 and 4.7 mg KOH/g to 25.4 mg KOH/g for NPT-21. The acid value of trisperma oil and biodiesel that had been stored for four months (27 °C, closed container) was also determined. Upon storage, the acid value of trisperma oil only slightly increased from 1.1 to 1.3 mg KOH/g. The acid value of stored biodiesel from trisperma oil also only slightly increased from 0.4 to 0.43 mg KOH/g.